PORE BREAKING OF HYDRAULIC PUMP COMPONENTS IN SINTERED STEEL - Cristina IONICI; Gabriela LEMNAR (Fiabilitate şi Durabilitate)
The geometrical structure of sintered steel pores and their distribution is described in terms of fractals. The found correspondence between pore distribution and crack is examined. The fractal dimensions of crack generated from pores model (due to the simple proposed geometrical rule) and real fatigue crack are compared.